Music video clip storyboard writing among focus group learners of media. - Abd Rahim, Normaliza (2011)

(untitled)
A storyboard is simply a sequence of drawings, similar to a comic book, which represents the sequence of shots in the finished screen work. It is essentially a timeline going from top to bottom, with the top occurring first. Hence, a storyboard is also an expression of everything or even a rough sketch that will be contained in the program telling where the menu screens in a computer interface will look like, what pictures either still or moving will be seen when and for how long, what audio and text will accompany the images, either synchronously or hyperlinked or in other words allows us to see what the scene will look like (Normaliza Abd Rahim et al., 2009). On the other hand, the storyboard expresses, in one way or another, everything that can be seen or heard or experienced by the end-user of the multimedia program. Therefore, this paper investigates the communication occurred during storyboard writing for the music video clip. Five pairs of subjects were involved in this study. A task was given to each pair and the length of time for them to discuss about the layout and the content of the storyboard was 3 hours for each pair in five weeks. The discussion will be taped and analyzed accordingly. The subjects were learners involved in a media course ages between 16-18 years old at one of the college sin Nottingham, six female and four male. The subjects had no experience in storyboard writing. They were to write the storyboard for a music video clip. This paper uses the ethnography communication theory by Hymes (1962) to analyze the conversations.